Pennsylvanian sponge from the Mecca Quarry Shale, Carbondale Group (Indiana, USA) and the paleobiogeographic distribution of Teganiella in the paleoequatorial region of Laurentia. (September 2019) - Mouro, Lucas D.; Horodyski, Rodrigo S.; Fernandes, Antonio. C.S.; Carvalho, Marcelo A.; Silva, Mateus. S.; Waichel, Breno L.; Saldanha, João P.
Abstract: The sponges may be the oldest group of Metazoa, with a long and successful evolutionary history. Despite their intermittent fossil record quality, the group has been considered reliable for paleoecological and paleobiogeographic analyses because they have inhabited various types of aquatic environments, forming a significant part of benthic communities. We have presented a detailed description of a new species from the genus Teganiella, Teganiella finksi new species, which expands the chronologic range and classifies the genus as endemic to the paleoequatorial regions of Laurentia associated with arid climate conditions linked to hypersaline periods. Combining the paleoecological and paleoenvironmental features of the Teganiella species, our findings also suggest a trend toward more closed-inlet conditions, which may be related to competition and/or specific habitat supplies, for example, heavy metals such as vanadium, zinc, and molybdenum. UUID: http://zoobank.org/12901a63-7cd5-4207-ac7a-0ce12649fcaf